The Egyptian uprising and April 6th Youth movement split - El Sayed, Somaia Metwalli (AUC Knowledge Fountain, 2014)
Few months after the Egyptian uprising, a considerable number of April 6th Youth movement announced their split. Knowing that the movement was already suffering from internal disputes over a number of issues, the research problem is centered on questioning whether and how the uprising played a role in such incident. Academic scholarship on social movements developed partial and action-oriented theories to explain different processes and dynamics of movement’s collective action. However, little work has been done on the trajectory of social movements in the Middle East, especially after radical forms of change as revolutions, uprisings or upheavals. It is argued that the Egyptian uprising played a role in April 6th Youth movement’s split. Using framing theory, the thesis’ main contribution is to examine the interplay between the external environment and the internal dynamics within the movement after the uprising, and how it influenced the unity of the movement using framing theory. The split can be explained as a failure in agreeing on framing the internal dispute or achieve a balance between the external pressure and the internal demands. Twelve in-depth interviews were conducted with members of both April 6th Youth movement and the Democratic Front’s. Covering the period from 2008 till April 2011, participants have been asked about: the main dimensions of the internal dispute prior to the uprising, their perception on the post-revolutionary setting, and the movement’s role, goals and strategies. Achieving balance in age, gender and governorates representation has been observed.